Supporting urban youth through social innovation: stronger together. - Adams, Eddy; Arnkil, Robert (My University, 2013)
Wie können Städte junge Menschen durch soziale Innovationen unterstützen? Dies ist die zentrale Frage des URBACT Arbeitskreises "Supporting Young People Through Social Innovation".

How can cities support young people through social innovation? This is the question that our URBACT workstream on "Supporting Urban Youth through Social Innovation" has explored.
Keywords: Sozialwandel; Sozialwesen; Innovation; Jugendlicher; Partizipation; Gesellschaft; Lebensbedingungen